Pengaruh Animasi pada Program Instruksional Pendidikan - M. Iqbal Arsyad; Herry Sujaini (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2004)
Computer Assisted Instruction (CAI) is instruction using computer as a means ofassist. From various aspects have an effect on to quality instructional software, problem liftedat this research is to see how far animation influence to result of student study by usinginstructional software.Method used at this research is with the use application instructional program usingaddition of animation facility to a group of sample, later then result of test of instructionitems compared to group sample of other dissimilar using instructional program withoutusing addition of animation facilityResult of research prove that happened by the difference which significant of betweensamples that is attempt group using instructional program additionally animation facility withthe group sample using instructional program without animation addition.Keyword: instructional software, animation